Regional-scale co-seismic landslide assessment using limit equilibrium analysis - Saade, Angela; Abou-Jaoude, Grace; Wartman, Joseph (Engineering geology, 2016)
Traditionally, regional assessment of seismic slope stability has been done using the infinite slope-rigid sliding block analysis. A major disadvantage of this approach is the resulting overestimation of the critical acceleration of the slope due to the underlying assumption of a predefined slope failure plane, and consequently the underestimation of hazard areas prone to sliding. In this paper, we present a modified approach for assessing seismic slope instabilities using a model based on limit equilibrium analysis and circular slip surfaces with no restriction to any predefined slope failure plane. For this purpose, we conduct a parametric study to identify the relationship between the critical acceleration of the slope, the slope angle, and the slope shear strength parameters. We model typical slopes in the Rocscience software SLIDE using Bishop's limit equilibrium method to identify the critical accelerations that corresponds to a failure plane with factor of safety equal to one. The critical accelerations were plotted against the variables in the parametric study and the best fit equations were obtained. The proposed approach was developed for global application but it was tested using the well-documented co-seismic landslide database of the 1994 Northridge, CA earthquake. The predicted sliding areas were compared to the inventory of landslides that were triggered in the Val Verde region in Los Angeles by the earthquake. Qualitative and quantitative assessments of the proposed model clearly show its advantages in predicting potential sliding areas. •A modified method is presented to assess regional coseismic landslide occurrences.•Bishop’s limit equilibrium analysis is applied using soil and rock yield criteria.•The method is validated using the 1994 Northridge, CA coseismic landslide database.•Qualitatively, the method predicts very well actual landslide locations.•Quantitatively, the method is very efficient in capturing the hazard areas.